Metode Dakwah Buya Fattal Yamin Dalam Pengajian Mingguan Di Masjid Taqwa Jorong Petok Nagari Panti Kabupaten Pasaman - M. Sukri; Penmardianto Penmardianto (KOLONI, 2023)
Buya Fattal Yamin is a preacher in weekly recitations which are held once in two weeks at the Taqwa Jorong Petok Nagari Panti Pasaman mosque. He uses bil-lisan da'wah in his study by using the bil-hikmah, mau'idhatul hasanah and mujadallah da'wah methods which seek to achieve the goals of da'wah and make it easier to implement so that the delivery can be easily understood by the congregation. The purpose of this study was to determine Buya Fattal Yamin's da'wah method in recitation at the Taqwa Jorong Petok Nagari Panti Pasaman mosque. This type of research is field research with a descriptive qualitative approach located at the Taqwa Jorong Petok Nagari Panti Mosque, Pasaman Regency. While collecting data by observation and interviews. The subject in this study was Buya Fattal Yamin while the object of research was Buya Fattal Yamin's da'wah method in recitation. The results of this study indicate that the preaching method of Buya Fattal Yamin in the weekly recitation at the Taqwa mosque is to use bil-lisan da'wah using the al-hikmah method, mau'idhatul hasanah (good teaching) and mujadallah (good discussion). The material presented is about aqidah, shari'ah, muamalah and morals. Keywords: Da'wah, Methods of Da'wah, Weekly Recitation